THE PATH OF THE BANK REGULATION AND INTERNATIONAL FINANCIAL CRISIS - Hennings Otoya, Julio Alberto (2011)
The world financial situation is in serious difficulties. The crisis originated in the country more Are you rich? land, whose explosion in 2007 in the U.S. mortgage sector made ancient and modern banking institutions, insurance, investment and related, some considered “too big to fail”, would pass into history as a painful example of the lack a prudent risk management, which are becoming more diverse and amplified by the globalization process that run the markets. Here, it is important to note that the administration of U.S. banking institutions, in an effort to “create value”, ergo earn more to satisfy their shareholders and above all to “meet the desires” inordinate of many managers, was stimulated in parallel by the lax measures the U.S. government, which undermined the possibilities for monitoring their financial institutions and the rational control of the whole system. This article describes and analyzes the history of banking regulation, the role played by the Bank for International Settlements and the results of the Committee on Banking Supervision by the Basel Accords, suggesting the omission of its implementation by U.S. institutions.